1194WebGIS in epidemiology: Lessons from LionVu Usability Assessment within Pennsylvania, United States. (2nd September 2021) - Geyer, Nathaniel; Kessler, Fritz; Lengerich, Eugene
Abstract: Focus of Presentation: LionVu, a web-based mapping tool using Leaflet JavaScript, was recently redesigned to better meet the needs of clinical, educational, and epidemiological audiences within Pennsylvania, United States, containing publicly available health-related and demographic data sets. In addition, the LionVu Usability Assessment, a 50-question online survey, was conducted to assess whether LionVu's functionality and improved interface met the needs of its intended audiences. The aim of this qualitative data analysis was to assess the themes of the open-ended questions of the LionVu Usability Assessment to improve the tool. Findings: Invitations to the LionVu Usability Assessment were sent in Spring 2020 (n = 123), with 23 who began (55% female), but only 10 completed the survey. The 23 participants were from academia (n = 10), professional settings (n = 10) or missing (n = 3). Six themes emerged as critical to improve LionVu's functionality: improving documentation and training materials, enhancing map customizability, including tabular displays below the maps, adjusting the colour schema, saving outputs as files, and displaying maps side-by-side. Conclusions/Implications: LionVu fills a niche in the health community by giving clinical, educational, and epidemiological audiences the ability to visualize and utilize health data at various levels of aggregations and geographical scales (i.e., state, county, zip code, etc.). Novel applications like LionVu can serve data for future purposes such as mapping and graphing in epidemiology. Key messages: The usability study of LionVu provided important feedback for its future development. Lessons and best practices on developing comparable WebGIS applications, for clinical, educational, and epidemiological audiences, are addressed.